1994
DOI: 10.1051/rnd:19940210
|View full text |Cite
|
Sign up to set email alerts
|

Composition des 3 types de foie gras : oie, canard mulard et canard de Barbarie

Abstract: — Nous avons comparé les 3 types de foie gras commercialisés en France : les foies gras d'oie, de canard mulard et de canard de Barbarie. Ces foies gras ont été obtenus à partir d'animaux élevés en même temps dans des conditions semblables et gavés à l'âge de 12 (canards) ou 13 sem (oies des Landes) pendant 13 j avec le même maïs : 11,7 kg/oie ; 10,7 kg/canard mulard et 8,1 kg/canard de Barbarie. Le poids des foies gras retenus pour cette étude (9 foies par type de palmipèdes, tous de sexe mâle) est en m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our results for average liver weight agreed with those reported by Beaza (12), Beaza et al (11), Petrov (3) and the producer of the hybrid when 84-day pre-force period was followed or slightly lower than those reported by Salichon et al (10) and Guy et al (14). Chartrin et al, 2006 (cited by 13) indicated a considerably lower liver weight in mulard drakes force-fed over 14 days and slaughter at 14 weeks of age  494 ± 97 g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results for average liver weight agreed with those reported by Beaza (12), Beaza et al (11), Petrov (3) and the producer of the hybrid when 84-day pre-force period was followed or slightly lower than those reported by Salichon et al (10) and Guy et al (14). Chartrin et al, 2006 (cited by 13) indicated a considerably lower liver weight in mulard drakes force-fed over 14 days and slaughter at 14 weeks of age  494 ± 97 g.…”
Section: Discussionsupporting
confidence: 93%
“…Wawro et al (9) reported final male mullards body weight of 3.150 kg at 12 weeks of age. Salichon et al (10) and Beaza (11) …”
Section: Discussionmentioning
confidence: 97%
“…The fatty acids disclosed an increase in saturated fatty acids and a decrease in linoleic acid content [30,31] . The data shown that palmitic (16:0), oleic (18:1) and linoleic (18:2) acids formed a majority of the fatty acid content in muscle tissues (Table 4…”
Section: Discussionmentioning
confidence: 99%
“…Les (Auvergne, 1992;Salichon et al, 1994), which is now commonly used for foie gras production. Studies carried out in geese and the muscovy duck have demonstrated that most of the lipid accumulated in the liver is triacylglycerol (Leclercq et al, 1968;Blum et al, 1990;Baudonnet-Lenfant et al, 1991).…”
mentioning
confidence: 99%